Response of overlying masonry structure induced by double track EPBM cutting through cemented soil composite pile foundation field measurements and numerical analysis - Xue-sen Li; Cheng Huang; Shi-ju Ma; Kai-rong Hong; Yong-gang Ding (Scientific Reports)
Abstract This article uses the engineering background of the Zhengzhou Metro Line 5 with a cement-soil group pile composite foundation. It simplifies the composite foundation using the area-weighted composite modulus method and establishes a finite element model of a double-line EPBM passing beneath the cement-soil group pile composite foundation building. The calculation results were compared and validated against monitoring data. Based on this, the simplified model was used to analyze the effects of face pressure and grouting pressure on the settlement of the upper structure. The research results indicate that the numerical simulation curves of settlement at monitoring points F17, F16, F15, and F14, where the shield axis intersects the building plane, align well with the monitored values, thereby confirming the rationality of the simplified model. Additionally, appropriately increasing the face pressure and grouting pressure is beneficial in suppressing the settlement of the upper structure; however, when the face pressure increases to 0.20 MPa and the grouting pressure increases to 0.35 MPa, the suppressive effect significantly diminishes.